Novel Metabolic Pathways Associated with Serum Bone Turnover Markers in Healthy Young Adults. (29th May 2020) - Roberts, Joseph; Bellissimo, Moriah; Taibl, Kaitlin; Uppal, Karan; Jones, Dean; Drissi, Hicham; Ziegler, Thomas; Alvarez, Jessica
Abstract: Objectives: Optimal bone health is maintained through a remodeling cycle consisting of resorption followed by formation. Procollagen type I N-terminal propeptide (P1NP) and C-terminal telopeptides of type I collagen (CTX) are biomarkers of bone metabolism that capture changes in bone formation and bone resorption, respectively. This study aimed to identify unique metabolic pathways related to bone turnover markers (BTMs) in healthy young adults. Methods: This cross-sectional study included 34 healthy, young adults (19 females, average age 27.8 years). Bone mineral density (BMD) was assessed by dual-energy x-ray absorptiometry. Fasting plasma was analyzed using dual column liquid chromatography and ultra-high-resolution mass spectrometry for metabolomics. Serum levels of P1NP and CTX were measured with ELISA. Linear regression and pathway enrichment analyses were used to identify metabolic pathways related to the BTMs. Results: All participants had a normal whole-body BMD T-score. Metabolites significantly associated with P1NP (at P < 0.05) were significantly enriched in pathways linked to the TCA cycle, pyruvate metabolism, and metabolism of B-vitamins important for energy production (e.g., niacin, thiamin). Other nutrition-related metabolic pathways associated with P1NP were amino acid (proline, arginine, glutamate) and vitamin C metabolism, which are important for collagen formation. Metabolites were associated with CTX levels (at P < 0.05), which were enriched within lipid and fatty acid beta-oxidation metabolic pathways, as well as fat soluble micronutrients pathways including, vitamin D metabolism, vitamin E metabolism, and bile acid biosynthesis. Conclusions: High-resolution metabolomics identified several distinct plasma metabolic pathways, including energy-yielding metabolic pathways and pathways related to fatty acid, amino acid, and micronutrient metabolism that were associated with markers of bone formation and bone resorption. Characterizing these metabolism-related pathways associated with BTMs in healthy adults is an important step towards understanding the metabolic perturbations that lead to low bone mass in older and clinical populations. Funding Sources: National Institutes of Health and Emory University.